El packaging como herramienta de comunicación: la incidencia del empaque de jugos de caja en la decisión de compra de las madres de NSB B de Lima Metropolitana - Pedraza Borja, Diana Fiorella (2021)
The main function of packaging has been to contain a product; however, with the increase of competition in the market, brands began to use it as a communication tool to differentiate themselves from others, create a brand image for their target audience, and ultimately lead to the final purchase decision. This work will analyze the influence of the design of natural juice packaging, including its colors, figure, shape, size, material, and the information on the label, on the purchase decision of the mothers of NSE B of Metropolitan Lima at the point of sale, according to their needs: Concern for the health of their children and for eating a healthy diet, practicality of use to save time, and the environmental sustainability care of the brand.